2009
DOI: 10.1161/strokeaha.108.531277
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health-Related Quality of Life After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Many patients who survive an aneurysmal subarachnoid hemorrhage experience decreased health-related quality of life (HRQoL). Physical factors have been identified as determinants of HRQoL. We describe long-term HRQoL and assessed whether psychological symptoms and personality characteristics determine HRQoL after subarachnoid hemorrhage. Methods-In a cross-sectional study in 141 patients living independently in the community 2 to 4 years after subarachnoid hemorrhage, we assessed whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(75 citation statements)
references
References 9 publications
2
70
0
3
Order By: Relevance
“…30 A Dutch cross-sectional questionnaire study of 141 patients, living independently after aSAH, reported 23% depression risk after aSAH according to Hospital Anxiety and Depression Scale. 32 This corresponds to the 20% risk of antidepressant use in patients with no symptoms after sIA-SAH according to mRS in our study.…”
Section: Strokesupporting
confidence: 50%
“…30 A Dutch cross-sectional questionnaire study of 141 patients, living independently after aSAH, reported 23% depression risk after aSAH according to Hospital Anxiety and Depression Scale. 32 This corresponds to the 20% risk of antidepressant use in patients with no symptoms after sIA-SAH according to mRS in our study.…”
Section: Strokesupporting
confidence: 50%
“…Clinical reports vary markedly in description of sustained anxiety disorders in SAH patients, with incidence estimates ranging from 0 to 40 % [30][31][32][33]. While the wide range in anxiety disorder prevalence may be due to methods of assessing anxiety and patient age [34], preclinical data from this study and other reports indicate that both severity and location of hemorrhage also may be contributory.…”
Section: Discussionmentioning
confidence: 62%
“…7 Furthermore, an individual's perception and establishment of goals and expectations are undoubtedly influenced by personal characteristics such as optimism, psychic stability, and confidence. 36 Not only were mental and personality functions identified as powerful determinants of HRQoL already in previous studies, [37][38][39] but the relationship between HRQoL and gait as well as activities of daily living (ADL), including housework, were also identified as determinants. 40,41 This association was in the chronic phase after stroke.…”
Section: Discussionmentioning
confidence: 96%